The Impact of Travel Influencers on Followers’ Attitudes and Visit Intention: A Study of Social Media Marketing in Tourism - JOY, JEENA; Dr. Gireesh Kumar G . S (Turizam, 2025)
Influencer marketing is an emerging trend in social media marketing. In the present study, we identified various factors which influence followers towards travel influencers and their impact on followers’ attitudes and visit intentions. The research population includes all social media users who follow any travel influencers on social media. Based on Ducoffes’ Advertising Value Model and Source Credibility Theory, three variables, such as entertainment, informativeness and source credibility, were identified and tested. The research employed a structured quantitative approach using a self administered questionnaire. 172 valid responses were collected and analysed using SPSS and AMOS SEM. The findings of the study show that the three factors entertainment, informativeness and source credibility have a significant positive impact on followers’ attitudes. However, source credibility has a more significant impact, followed by entertainment and informativeness. Also, the study reveals that a positive attitude among followers enhances the intention to visit the destination recommended by travel influencers. These findings help destination marketers and tourism operators to create more useful influencer marketing campaigns. Further, future researchers can expand the current research model by adapting more factors which impact followers’ attitudes and visit intention.